2015
DOI: 10.4103/0019-5413.156229
|View full text |Cite
|
Sign up to set email alerts
|

Ewing’s sarcoma of proximal phalanx of the hand with skip metastases to metacarpals

Abstract: Ewing's sarcoma is the second most common malignant primary bone tumor of childhood and adolescence affecting mainly the diaphysis of long bones and flat bones. This tumor is extraordinarily rare in small bones of the hand and presents as a swelling with atypical radiological features of cystic and lytic lesion with scant periosteal reaction. The common differential diagnosis include osteomyelitis, tuberculosis, enchondroma and benign tumors. Moreover, skip metastasis to adjacent bones is even rarer. The progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Thus, CT of the chest and bilateral bone marrow biopsies are typically performed at diagnosis [ 1 , 13 ]. Several studies now demonstrate that primary tumors involving the distal extremities reliably favor a better prognosis [ 1 , 3 , 5 ]. This advantage is likely a consequence of their relative isolation and smaller tumor size at presentation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CT of the chest and bilateral bone marrow biopsies are typically performed at diagnosis [ 1 , 13 ]. Several studies now demonstrate that primary tumors involving the distal extremities reliably favor a better prognosis [ 1 , 3 , 5 ]. This advantage is likely a consequence of their relative isolation and smaller tumor size at presentation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 20% of these cancers may present in soft tissues with reports detailing involvement of almost every major organ [1,2]. Ewing's sarcoma of the hand is extremely rare with less than 25 cases reported to date [3][4][5][6][7][8][9][10][11][12]. A small review suggests that Ewing's sarcoma of the hand most commonly involves the proximal phalanx of either the thumb or third digit [3].…”
Section: Introductionmentioning
confidence: 99%
“…Metaphyseal localization in the hand bones are possible but have never been described. Several studies showed that subacute osteomyelitis occurs each time there is a decreased bacterial virulence and an increased host resistance [5][6][7]. Moreover, early antibiotic therapy in acute form seems to have a rule in occurrence of subacute form since it decreases the virulence of infectious agents [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…When the possibility of this tumor is confronted in patients older than 30, the physician must first exclude small-cell carcinoma and large-cell lymphoma from the list of differential diagnoses ( 2 ). Although this tumor is stated to comprise almost 6% of the total malignant bone tumors, it is very rare in the small bones of the hands and feet, where the incidence is not more than 1% ( 3 ). The foot bones most commonly involved include the calcaneus and the metatarsals ( 4 ).…”
Section: Introductionmentioning
confidence: 99%